The financial burden of out-of-pocket expenses in the United States and Canada: How different is the United States? - Baird, Katherine E (SAGE Open Med, 2016)
BACKGROUND: This article compares the burden that medical cost-sharing requirements place on households in the United States and Canada. It estimates the probability that individuals with similar demographic features in the two countries have large medical expenses relative to income. METHOD: The study uses 2010 nationally representative household survey data harmonized for cross-national comparisons to identify individuals with high medical expenses relative to income. Using logistic regression, it estimates the probability of high expenses occurring among 10 different demographic groups in the two countries. RESULTS: The results show the risk of large medical expenses in the United States is 1.5–4 times higher than it is in Canada, depending on the demographic group and spending threshold used. The United States compares least favorably when evaluating poorer citizens and when using a higher spending threshold. CONCLUSION: Recent health care reforms can be expected to reduce Americans’ catastrophic health expenses, but it will take very large reductions in out-of-pocket expenditures—larger than can be expected—if poorer and middle-class families are to have the financial protection from high health care costs that their counterparts in Canada have.